2020
DOI: 10.7554/elife.55529
|View full text |Cite
|
Sign up to set email alerts
|

Smchd1 is a maternal effect gene required for genomic imprinting

Abstract: Genomic imprinting establishes parental allele-biased expression of a suite of mammalian genes based on parent-of-origin specific epigenetic marks. These marks are under the control of maternal effect proteins supplied in the oocyte. Here we report epigenetic repressor Smchd1 as a novel maternal effect gene that regulates the imprinted expression of ten genes in mice. We also found zygotic SMCHD1 had a dose-dependent effect on the imprinted expression of seven genes. Together, zygotic and maternal SMCHD1 regul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 86 publications
8
57
1
Order By: Relevance
“…First identified as a regulator of variegation in the mouse (Blewitt et al, 2005), Smchd1 is required for proper X inactivation and regulates large gene clusters such as Hox or Pcdh loci and imprinted genes chromatin (Blewitt et al, 2008;Brideau et al, 2015;Gdula et al, 2019;Gendrel et al, 2012;Jansz et al, 2018;Mason et al, 2017;Massah et al, 2014;Wang et al, 2018;Wanigasuriya et al, 2020). At the 2 cell stage, Smchd1 shields against active Tetdependent DNA demethylation (Huang et al, 2021) and plays a predominant role in autosomal imprinting through a maternal effect (Ruebel et al, 2019;Wanigasuriya et al, 2020). However, the role of this protein in human tissues remain partially understood despite its implication in a number of distinct rare genetic diseases linked to heterozygous SMCHD1 mutation (Gordon et al, 2017;Kinjo et al, 2020;Lemmers et al, 2012;Shaw et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First identified as a regulator of variegation in the mouse (Blewitt et al, 2005), Smchd1 is required for proper X inactivation and regulates large gene clusters such as Hox or Pcdh loci and imprinted genes chromatin (Blewitt et al, 2008;Brideau et al, 2015;Gdula et al, 2019;Gendrel et al, 2012;Jansz et al, 2018;Mason et al, 2017;Massah et al, 2014;Wang et al, 2018;Wanigasuriya et al, 2020). At the 2 cell stage, Smchd1 shields against active Tetdependent DNA demethylation (Huang et al, 2021) and plays a predominant role in autosomal imprinting through a maternal effect (Ruebel et al, 2019;Wanigasuriya et al, 2020). However, the role of this protein in human tissues remain partially understood despite its implication in a number of distinct rare genetic diseases linked to heterozygous SMCHD1 mutation (Gordon et al, 2017;Kinjo et al, 2020;Lemmers et al, 2012;Shaw et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanism, likely dependent on Xist or H3K27me3 enrichment, underlying this process remains partially understood. Smchd1 is also implicated in the regulation of heterochromatin, repetitive DNA sequences or clustered imprinted genes and monoallelically expressed Protocadherin genes (Blewitt et al, 2008;Blewitt et al, 2005;Brideau et al, 2015;Gendrel et al, 2013;Mason et al, 2017;Massah et al, 2014;Mould et al, 2013;Nozawa et al, 2013;Wanigasuriya et al, 2020). SMCHD1 has also been found at telomeres with a direct correlation between telomere length and SMCHD1 enrichment (Dejardin and Kingston, 2009;Grolimund et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously studied SMCHD1 extensively in X chromosome inactivation, development, its effects in gene regulation as well as its role in organising the genome. It has been shown that SMCHD1 plays a role in Hox gene regulation 14 , clustered protocadherin gene expression 10; 11; 13 , in mediating long-range chromatin interactions 14; 31-33 , and in canonical and noncanonical imprinting 12 . Moreover, variants in SMCHD1 that have differing outcomes on SMCHD1 function are associated with two different diseases: FSHD and BAMS 15; 27 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a sensitised in vivo screen in mice that paired N-ethyl-N-nitrosourea (ENU) mutagenesis with a variegating GFP transgene array to identify modifiers of transgene variegation, and therefore epigenetic regulation 7 . This screen led to the discovery of the Smchd1 gene that encodes an epigenetic repressor, since shown to play a role in X-chromosome inactivation 8; 9 , silencing of clustered gene families such as select imprinted clusters [10][11][12] , the clustered protocadherins 10; 11; 13 and Hox genes 14 . By understanding more about SMCHD1 we can also learn more about how gene silencing works in each of these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis was carried out using R-language (R-project.org) and packages available through the Bioconductor project (www.bioconductor.org). Normalization factors to scale RNA-seq library size were calculated using TMM method (Robinson and Oshlack, 2010; Wanigasuriya et al, 2020) and converted to counts per million (CPM) reads using the cpm function (edgeR package). Gene transcripts with a CPM >1 in at least one sample were kept for further analysis.…”
Section: Methodsmentioning
confidence: 99%